TUJUAN PENCIPTAAN MANUSIA DAN FUNGSI LEMBAGA-LEMBAGA PENDIDIKAN - Muhammad Hasan (Hunafa: Jurnal Studia Islamika, 2010)
God created all His creatures based on His might. He created human beings in the best form with combination   of physics, reason, and spirituality. The experts in education have a concensus that to organize the civilization of human beings, education must  be based on the proporrtional education demenstions, namely the balance between the physics and the spituality.Kata Kunci: penciptaan manusia, fungsi lembaga pendidikan